Analysis of Micro Business Marketing Strategy in Facing Competition - Hia, Asroni; Lahagu, Arianto; Laoli, Eka Septianti; Telaumbanua, Wahyutra Adilman (Golden Ratio of Data in Summary, 2024)
This study is motivated by the challenges faced in the development of micro-enterprises at Bukit Sion Market, largely due to the high level of competition. Many businesses struggle to determine appropriate financing models and product offerings, as the market is saturated with similar products offered by competitors. The objective of this research is to analyze the marketing strategies employed by micro-enterprises and identify the obstacles they face in dealing with competition at Bukit Sion Market, Lahomi District. The research employs a descriptive qualitative method. The findings reveal that all food stalls adopt marketing strategies that include market selection, product planning, pricing, distribution systems, and marketing communication. Effective marketing strategies, such as offering discounts, special promotions, or hosting promotional events, have been shown to significantly boost sales. However, the food stalls encounter several challenges, including intensified competition due to the emergence of similar businesses offering comparable products, a lack of product innovation and promotion, fluctuations in raw material prices, as well as issues with product quality consistency, customer service, and overall customer experience.